Longitudinal Assessment of Cortical Excitability in Children and Adolescents With Mild Traumatic Brain Injury and Persistent Post-concussive Symptoms - King, Regan; Kirton, Adam; Zewdie, Ephrem; Seeger, Trevor A.; Ciechanski, Patrick; Barlow, Karen M. (Frontiers in Neurology, 2019)
Introduction: Symptoms following a mild traumatic brain injury (mTBI) usually resolve quickly but may persist past three months in up to 15% of children. Mechanisms of mTBI recovery are poorly understood, but may involve alterations in cortical neurophysiology. Transcranial Magnetic Stimulation (TMS) can non-invasively investigate such mechanisms, but the time course of neurophysiological changes in mTBI are unknown. Objective/Hypothesis: To determine the relationship between persistent post-concussive symptoms (PPCS) and altered motor cortex neurophysiology over time. Methods: This was a prospective, longitudinal, controlled cohort study comparing children (8-18 years) with mTBI (symptomatic versus asymptomatic) groups to controls. Cortical excitability was measured using TMS paradigms at one and two months post injury. The primary outcome was the cortical silent period (cSP). Secondary outcomes included short interval intracortical inhibition (SICI) and facilitation (SICF), and long-interval cortical inhibition (LICI). Generalized linear mixed model analyses were used to evaluate the effect of group and time on neurophysiological parameters. Results: One hundred seven participants [median age 15.1, 57% female) including 78 (73%) with symptomatic PPCS were compared to 26 controls. Cortical inhibition (cSP and SICI) was shorter in the symptomatic group compared to asymptomatic group and tended to increase over time. Measures of cortical facilitation (SICF and ICF) were increased the asymptomatic group and decreased over time. TMS was well tolerated with no serious adverse events. Conclusions: TMS-assessed cortical excitability is altered in children following mild TBI and is dependent on recovery trajectory. Our findings support delayed return to contact sports in children even where clinical symptoms have resolved.